Development of media presentation through application to 4.0 based learning optimization - Soeparno, Wahyu Sugeng Imam; Hasyim, Sirojuzilam; Rahman, Arif; Andrasari, Monika; Simatupang, Dewi Ratna Sari; Siahaan, Nico Bayu Gilbert (Talenta Publisher Universitas Sumatera Utara, 2024)
Sekolah Indonesia Bangkok (SIB) faces challenges in utilizing online presentation platforms such as Canva, Prezi, and Slidebean. Both students and teachers have limited understanding of advanced features, leading to low-quality presentations and limited creativity in delivering lesson materials. Additionally, no formal training has been provided to maximize the use of these tools in the school environment. Students also get learning materials or guidebooks accompanied by learning stationery, as well as practical materials in the form of online platform web links that are ready to be processed. The guidebook given to the students is not limited to the training, but can be used outside of the training session. The learning method used in these learning activities is project-based learning where students will get an understanding of the benefits of creativity in presentation media and material on the use of online platforms 4.0, then continued with practical sessions where students are directed to implement the material received with online platforms provided through website links. The benefits of this community service activity are determined by considering the cognitive and psychomotor aspects demonstrated by the students. Based on the results of pre-test and post-test conducted on 35 participants, there was an average increase of 45% in students understanding of the use of the Canva, Prezi, and Slidebean platforms. Before the training, only 30% of students understood the basic features of these platforms, while after the training, this number increased to 75%.